Consistent Iodine Status Assessment in Chinese Adults by Different Spot Urinary Iodine Concentrations in a Day Together With Corresponding Correction Coefficients. (3rd October 2019) - Liu, Wendi; Zhang, Peng; Zhao, Xin; Sang, Maocheng; Liu, Xiaotong; Liu, Lu; Liu, Shiyan; Lin, Haiyue; Sang, Zhongna
Abstract: Objective: The aim of this research was to determine the correction coefficients of different spot urinary iodine concentrations (UICs) in a day to predict the early morning UIC, to make the different spot UICs of a day comparable in assessing iodine status in the same population. Methods: In total, 424 participants aged 18 to 28 years were recruited from Tianjin, China. Three spot urine samples were collected from each participant during three periods of the day (6:30–7:00, 10:00–10:30, and 16:00–16:30). A total of 1272 urine samples were collected. A 24-hour dietary record was reported by each participant for 3 consecutive days. Results: Both the UICs at 10:00–10:30 and 16:00–16:30 were higher than that at 6:30–7:00 (181.75 or 198.15μg/L vs 157.69 μg/L; all p  < 0.05). Bland-Altman plot showed no good agreements between the other two spot UICs and that at 6:30–7:00 with both Bland-Altman indexes of 7.1%. Correction coefficients used to predict UIC at 6:30–7:00 from the UIC at 10:00–10:30 and 16:00–16:30 were 0.9231 and 0.8592, respectively. The predicted UICs at 6:30–7:00 by using the UIC at 10:00–10:30 and 16:00–16:30 both had no statistically significant difference with the actual UIC at 6:30–7:00 (all p  > 0.05). Bland-Altman plot showed good agreements between the predicted UICs and actual UICs at 6:30–7:00 with both Bland-Altman indexes of 4.5%. Conclusions: It was reliable to predict the early morning UIC using correction coefficients of other spot UIC of the day, which gave a new idea for standardizing the methodology of surveys assessing iodine status of a population.